Linezolid-induced black hairy tongue - Braggio, Cesare; Bocchialini, Giovanni; Ventura, Luigi; Carbognani, Paolo; Rusca, Michele; Ampollini, Luca (Acta Biomedica Atenei Parmensis, 2018)
Black hairy tongue (BHT) is a self-limiting disorder characterized by abnormal hypertrophy and elongation of filiform papillae on the surface of the tongue. The exact mechanism of drug-induced BHT is unknown. Several factors have been implicated and included smoking or chewing tobacco, drinking alcohol, poor oral hygiene and antibiotics such as tetracyclines and penicillins. We report a quite uncommon case of Linezolid-induced BHT in a patient with a long-lasting history of chest wall infection